Car Transfer and Wheelchair Loading Techniques in Independent Drivers with Paraplegia - Haubert, Lisa Lighthall; Mulroy, Sara J.; Hatchett, Patricia E.; Eberly, Valerie J.; Maneekobkunwong, Somboon; Gronley, Joanne K.; Requejo, Philip S. (Frontiers in Bioengineering and Biotechnology, 2015)
Car transfers and wheelchair (WC) loading are crucial for independent community participation in persons with complete paraplegia from spinal cord injury, but are complex, physically demanding, and known to provoke shoulder pain. This study aimed to describe techniques and factors influencing car transfer and WC loading for individuals with paraplegia driving their own vehicles and using their personal WCs. Sedans were the most common vehicle driven (59%). Just over half (52%) of drivers place their right leg only into the vehicle prior to transfer. Overall, the leading hand was most frequently placed on the driver’s seat (66%) prior to transfer and the trailing hand was most often place on the WC seat (48%). Vehicle height influenced leading hand placement but not leg placement such that driver’s of higher profile vehicles were more likely to place their hand on the driver’s seat than those who drove sedans. Body lift time was negatively correlated with level of injury and age and positively correlated with vehicle height and shoulder abduction strength. Drivers who transferred with their leading hand on the steering wheel had significantly higher levels of shoulder pain than those who placed their hand on the driver’s seat or overhead. The majority of participants used both hands (62%) to load their WC frame and, overall, most loaded their fame into the back (62%) vs. the front seat. Sedan drivers were more likely to load their frame into the front seat than drivers of higher profile vehicles (53% vs. 17%). Average time to load the WC frame (10.7 seconds) was 20% of the total WC loading time and was not related to shoulder strength, frame weight or demographic characteristics. Those who loaded their WC frame into the back seat had significantly weaker right shoulder internal rotators. Understanding car transfers and WC loading in independent drivers is crucial to prevent shoulder pain and injury and preserve community participation.